Effect of patoladi ghanasara on ethanolinduced gastric lesions in rats - Munasinghe, S.L.; Vithanage, D.K.; Ratnasooriya, W.D. (My University, 2002)
Patoiadi Ghanasara (PG) consist:.;:\ of five ingredients (Termimlia chebule Retz; Terminania belarica Roxb, Phillenthus emblica Linn; Tricosenthus cucumarina Linn; Azadirachta indica A Juss) is recommended for the treatment of gastric lesions (Amlapitta) in Ayurvedic medicine. R&cently, we showed using rat ethanol-induced gastric lesion technique that Patoiadi decoction has strong gastroprotective activity when given orally. The aim of this study was to investigate whether semisolid preparation of this decoction, namely (PG) has gastroprotective activity when assessed with the same technique and method of administration. Three different concentrations of the PG were used: 30%, 15% and 7-5%. The results show that PG has overall gastroprotective activity but is less effective than PD (in terms of both number and length of gastric haemorrhgic lesions